Penerapan Ekstraksi Warna Alami Pelepah Pisang Kepok (Musa Paradisiaca) untuk Pencelupan Kain Katun Primisima - Nisa, Atina Khoiron; Dasining, Dasining; Mukaromah, Habibatul; Hanifah, Siti Nur; Siami, Siti Nur; Mu'imamah, Rosita Selvina Putri (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Natural substance coloring comes from natural ingredients that are the result of plant extracts, such as banana fronds that contain tannins in their sap and produce brown pigments. Dyeing of natural substances can be done using tunjung mordan and using Primisima cotton fabric. Primisima is a type of cotton with better quality than other types of cotton, with fine and thick fibers. This study aims to find out how to apply Primisima cotton fabric in the natural dyeing of kepok banana fronds using alum mordan (Al2SO4)3, lime (CaCO3), and tunjung (Fe(SO4)3) with dyeing techniques. The mordanting process is carried out in three ways, namely pre-mordan, simultaneous, and post-mordan, then fixed to lock the natural dyes of the mordan group and provide a more permanent color effect. The novelty of this research lies in the selection of natural dye materials from the fronds of the kepok banana and the use of different mordan combinations to obtain variations in color results in Primisima cotton fabric. Based on the dyeing results, the pre-mordan using the three mordans produces brown color and color flatness in the flat category, simultaneously produces light brown color with uneven color flatness, and post-mordan produces brown color with uneven color flatness. The best results were obtained by using the tunjung mordan on the pre-mordan, compared to simultaneous and post-mordan.